If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(2x + -5) + (3x + 4)(6x + -1) = 0 Reorder the terms: X(-5 + 2x) + (3x + 4)(6x + -1) = 0 (-5 * X + 2x * X) + (3x + 4)(6x + -1) = 0 (-5X + 2xX) + (3x + 4)(6x + -1) = 0 Reorder the terms: -5X + 2xX + (4 + 3x)(6x + -1) = 0 Reorder the terms: -5X + 2xX + (4 + 3x)(-1 + 6x) = 0 Multiply (4 + 3x) * (-1 + 6x) -5X + 2xX + (4(-1 + 6x) + 3x * (-1 + 6x)) = 0 -5X + 2xX + ((-1 * 4 + 6x * 4) + 3x * (-1 + 6x)) = 0 -5X + 2xX + ((-4 + 24x) + 3x * (-1 + 6x)) = 0 -5X + 2xX + (-4 + 24x + (-1 * 3x + 6x * 3x)) = 0 -5X + 2xX + (-4 + 24x + (-3x + 18x2)) = 0 Combine like terms: 24x + -3x = 21x -5X + 2xX + (-4 + 21x + 18x2) = 0 Reorder the terms: -4 + -5X + 21x + 2xX + 18x2 = 0 Solving -4 + -5X + 21x + 2xX + 18x2 = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4' to each side of the equation. -4 + -5X + 21x + 2xX + 4 + 18x2 = 0 + 4 Reorder the terms: -4 + 4 + -5X + 21x + 2xX + 18x2 = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5X + 21x + 2xX + 18x2 = 0 + 4 -5X + 21x + 2xX + 18x2 = 0 + 4 Combine like terms: 0 + 4 = 4 -5X + 21x + 2xX + 18x2 = 4 Add '-21x' to each side of the equation. -5X + 21x + 2xX + -21x + 18x2 = 4 + -21x Reorder the terms: -5X + 21x + -21x + 2xX + 18x2 = 4 + -21x Combine like terms: 21x + -21x = 0 -5X + 0 + 2xX + 18x2 = 4 + -21x -5X + 2xX + 18x2 = 4 + -21x Add '-18x2' to each side of the equation. -5X + 2xX + 18x2 + -18x2 = 4 + -21x + -18x2 Combine like terms: 18x2 + -18x2 = 0 -5X + 2xX + 0 = 4 + -21x + -18x2 -5X + 2xX = 4 + -21x + -18x2 Reorder the terms: -4 + -5X + 21x + 2xX + 18x2 = 4 + -21x + -18x2 + -4 + 21x + 18x2 Reorder the terms: -4 + -5X + 21x + 2xX + 18x2 = 4 + -4 + -21x + 21x + -18x2 + 18x2 Combine like terms: 4 + -4 = 0 -4 + -5X + 21x + 2xX + 18x2 = 0 + -21x + 21x + -18x2 + 18x2 -4 + -5X + 21x + 2xX + 18x2 = -21x + 21x + -18x2 + 18x2 Combine like terms: -21x + 21x = 0 -4 + -5X + 21x + 2xX + 18x2 = 0 + -18x2 + 18x2 -4 + -5X + 21x + 2xX + 18x2 = -18x2 + 18x2 Combine like terms: -18x2 + 18x2 = 0 -4 + -5X + 21x + 2xX + 18x2 = 0 The solution to this equation could not be determined.
| 3x^2+42x+441=0 | | 73x-15=48+99 | | x+(x*.04)=2.75 | | (x+0.2)(x+3.9)=0 | | 28d+1=28 | | x^2+4x+28=0 | | x+x(.04)=2.75 | | 3(7-2h)=9 | | x^2=y-1 | | -s+3=52+21 | | x^2+34x+2= | | -x^2+565x-8250=0 | | (x-y)(x^2-10xy+y^2)=0 | | b-[x+4a+(x-7)]= | | 9+4+4v-2v+6=11 | | 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) | | 144=4q+4q | | 4x-3=3(-1+x) | | x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 | | X+2x-1=2(-1+x) | | (4x^2-9x-9)= | | -x^2+515x-7500=0 | | 10x-45=3(b-15) | | h(t)=196-16t^2 |